Assembly of the Mitochondrial Membrane System. Purification of a Mitochondrial Product of the ATPase - Sierra, Marcelino F. (1973)
A low-molecular-weight protein synthesized in yeast mitochondria was purified. The protein was identified as a component of the rutamycin-sensitive ATPase. The amino-acid composition of the purified protein shows an extremely large preponderance of nonpolar residues, which may account for its solubility in chloroform-methanol. Indirect evidence suggests that this component is involved in the conferral of rutamycin sensitivity and may also have a function in the assembly of the ATPase complex.